The Practice Of Physical Sports Activities And Its Relationship With Academic Achievement In Light Of The Introduction Of A New Curriculum And A Specialized Teacher In The Primary Education Stage (a Field Study Of Primary Schools In The Wilaya Of Touggour - Maamri , Mahmoud; Ouanouki , Yahia (sports creativity, 2025)
Believing in the importance of physical education and its effective role in shaping the learner's personality at every educational stage, especially in the primary education stage, our study aims to shed light on the topic of practicing physical sports activities and their relationship with academic achievement among primary school students in light of the presence of a new curriculum and a specialized teacher. This is a field study conducted on the teachers of primary schools in the Wilaya of Touggourt.